Analysis of factors affecting on low profits gained by paddy farmers with special reference to farmers in matara district - Abeywardana, C.P.; Nishadi, G.P.K. (university of Jaffna, 2014)
Paddy and rice are particularly important for resource poor households, both as a cultivated crop and also as a major constituent of diets in rural and urban areas. At present,the sector is facing an unparalleled crisis which is rapidly pushing the sector towards more vulnerability. Due to inconsistency of the findings in the literature and lack of substantial number of recent studies conducted in the Sri Lankan context, factors affectıng on low profıts gaıned by paddy farmers in Matara district remains unclear. So, the main objective of this study is to analyze the factors which are influecing on low profit earned by the paddy farmers. The study was carried out in Matara district and primary data were collected from a sample of 100 farmers by using a negatively ranked five point lickert scale. Basically, the root causes for the low profit were measured based on six variables as Cost of production, Middlemen involvement, Inadequacy of market information, Inadequacy of infrastructure facilities, Land size and ownership style and Time of selling paddy. Results indicated that higher cost of production is the first and foremost important factor which reduces farmers' net profit while lower land size and non-ownership and the time of selling the paddy were considered as the other important factors. However, middlemen involvement, inadecquacy of market information and infrastructure have a relatively moderate and lower impact to change the profits earned from the business.
Keywords: Paddy farmers; Low profit; Influential factors